Detection of major impact damage to composite aerospace structures by ultrasonic guided waves and statistical signal processing. (2017) - Capriotti, M.; Kim, H.E.; di Scalea, F. Lanza; Kim, H.
Abstract: The detection of major damage to composite aerospace structures, specifically damage to skins, stringers and frames, remains a challenge of NDE tests performed from the skin side. Damage to the internal structures can be caused, for example, by ground vehicle impacts which are characterized by large impact force magnitudes with relatively long time scales. An approach will be presented to detect such damage by accessing the skin side, based on an ultrasonic guided wave differential scheme. Statistical processing is applied to the measurements to normalize the test for the normal "baseline" of the test structure so as to maximize the Probability Of Detection (POD) and minimize the Probability of False Alarms (PFA). The performance of the proposed method is quantified by the computation of Receiver Operating Characteristics (ROC) curves that show the compromise between POD and PFA obtainable with varying detection thresholds. In addition, the potential for utilizing air-coupled transducers for non-contact scanning will be discussed.